STRATIGRAFI DAERAH TIMIKA DAN SEKITARNYA, PAPUA - Kusnama Kusnama (Jurnal Geologi dan Sumberdaya Mineral, 2008)
The rocks succession exposed in the Timika area, Papua, have an age ranging from Precambrian to Quaternary. The oldest rock is the Nerewip Formation consisting of pillow lava and basalt intercalated with foliated meta-sedimentary rocks and overlies unconformably and paraconformably by the Otomona Formation which is dominated by slate and sandstone and also metamorphosed of Precambrian-Cambrian in age. On top of the Otomona Formation is overlain unconformably the Tuaba Formation which consists mainly of sandstone, and red mudstone in the upper part. The age of this formation is not younger than Ordovician. The Siluro-Devonian Modio Formation comprises predominantly dolomite and minor clastic sediments lying disconformably on the Tuaba Formation. The overlying coarser upward sequence Aiduna Formation with a shallow marine to deltaic environment, overlies unconformably the Modio Formation consisting of alternating of sandstone and carbonaceous mudstone, intercalated by bio-calcarenite and coal beds, probably of Permian in age. On top of this formation was conformably deposited the red beds Tipuma Formation of a terrestrial origin. The age of the formation is thought to be Triassic to Early Jurassic. The Kembelangan Group of Middle Jurassic to Late Cretaceous comprises of intercalating of quartz sandstone and mudstone which are rich in ammonite fossils overlies unconformably the Tipuma Formation. The Tertiary sequence which is dominated by carbonate platform having rich in large foraminifera of the New Guinea Limestone Group lying conformably on the Kembelangan Group. The age of this group is Paleocene to Early Miocene. The Late Miocene to Pliocene Buru Formation consist of alternating of sandstone and mudstone overlying conformably the Nugini Limestone Group. The Diorite intrusion in this unit in Late Tertiary resulted a favourable Au/Cu mineralization in the formation, in north of Timika (the Central Range of Papua). The Quaternary deposits are widespread in the southern part of south Timika area. Keywords : Papua, Timika, Stratigraphy, Diorite intrusion, Precambrium,Paleozoic, Mesozoic, and Tertiary